PTH-066 Cholangioscopy-Assisted Electrohydraulic Lithotripsy is Highly Effective in the Management of Difficult Bile Duct Stones. (4th June 2013) - Lekharaju, V P K; Noorullah, O; Kumar, M; Wadsworth, C A; Kaltsidis, C; Shearer, E S; Dwyer, L; Webster, G J M; Sturgess, R
Abstract : Introduction: Although conventional endoscopic techniques for the removal of stones from the biliary tree are highly effective, they fail in up to 10% of patients with choledocholithiasis. With the introduction of single operator peroral cholangioscope (POC), the SpyGlass ® System, stone fragmentation under direct visual control has proven to be highly effective and is now emerging as an important endoscopic therapy. We describe the characteristics and outcomes of patients undergoing POC directed electrohydraulic lithotripsy (POC-EHL) in two tertiary Hepatobiliary units in England. Methods: Details of all patients undergoing POC-EHL at Aintree University Hospital and University College London Hospitals were prospectively recorded. Data collected included demographics, number of ERCPs, site of the stone, number of POC-EHL sessions, success of stone clearance and complications. Results: A total of 93 patients were referred for POC-EHL. There were 25 males (27%) and 68 females (73%). The median age was 65 (20–92) years. 71 (76%) patients were tertiary referrals. 62 (67%) patients had at least two or more endoscopic attempts at stone removal prior to referral for POC-EHL. In six patients POC-EHL was not required because at ERCP prior to POC, the ducts could be cleared with conventional techniques. In five patients EHL was not attempted due to the size, configuration and quantity of stones. With the knowledge that these patients were fit for cholecystectomy, they were referred for cholecystectomy and bile duct exploration as a one-stage procedure. All POC-EHL sessions were performed under general anaesthesia. Of the 82 patients undergoing POC-EHL 61 (75%) patients needed one POC-EHL session and 10 (12%) required two sessions and 6 (7%) required three sessions for complete stone extraction. In 5/82 (6%) complete stone extraction was not possible despite POC-EHL and these patients were referred for surgery. The sites of stones were common bile duct in 48%, cystic duct and CBD in 20%, cystic duct in 4%, common hepatic duct in 10% and intra-hepatic ducts in 18%. Three patients developed cholangitis post POC-EHL, responding to antimicrobial therapy. Two patients experienced post-procedure bleeding, only one patient required endoscopic intervention. Conclusion: On an intention to treat basis, 89% of patients referred for POC-EHL were treated successfully. Successful POC-EHL frequently requires combination with other stone removal techniques including mechanical lithotripsy. POC-EHL appears to be a safe and effective technique in the clearance of refractory biliary stones. Disclosure of Interest: None Declared.